Current Perspective on Residual Knowledge Gaps in the Assessment of Transporter‐Mediated Drug Interactions. Issue 3 (20th June 2022) - Yang, Xinning; Reynolds, Kellie; Madabushi, Rajanikanth; Huang, Shiew‐Mei
Abstract : Assessment of transporter‐mediated drug–drug interaction (DDI) is integral to drug development. A risk‐based approach leveraging in vitro, in vivo, and in silico information is used to evaluate the DDI liability of drugs and inform the instructions of use. While tremendous advances have been made in recent decades, there are knowledge gaps warranting further research. Herein, we focus on select areas to advance assessment of DDI potential for drugs as substrates, inhibitors, or inducers of certain transporters.